Environmental economics : in theory and practice - Hanley, Nick.; Shogren, Jason F.; White, Ben (Benedict) (Basingstoke [England] ; New York : Palgrave Macmillan, 2007)
Environmental Economics in Theory and Practice is an ideal text for students taking advanced courses in environmental and natural resource economics.
Economy Environment Interactions.- Sustainable Development.- Market Failure.- Incentive Design.- Emission Taxes and Tradable Emission Permits: Theory into Practice.- Transboundary and Global Pollution.- Nonrenewable Resources: Market Structure and Policy.- Nonrenewable Resource Scarcity, Costs, and Externalities.- Biological Natural Resources: the Fishery.- Forestry Economics.- Theory and Methods for Environmental Valuation.- Environmental Risk.- Trade and the Environment.
Includes bibliographical references and indexes.
Keywords: Environmental economics